Asian Taste / Nurjeha Ramli ... [et al.] - Ramli, Nurjeha; Zakaria, Nurul Izzati; Zainil Abaddin, Siti Zulaikha; Abdullah, Fatin Nurshahirah Iwana; Mohd Riffin, Muhammad Arif Aiman (2021)
When we travel to a foreign country, we always seek for its famous and traditional dish. Every region in each country has their own unique traditional dish in which it has been passed on for decades or generations. As those dishes becomes more famous and known, we would really want to have a taste of it and that is the reason of why we decided to build Asian Taste. Asian taste is restaurant which specialized on Asian famous and traditional noodle dishes established on January 2021. Our restaurant is located at 23, Jalan Kristal K7/K, Seksyen 7, 40000 Shah Alam, Selangor Darul Ehsan and we are open on Monday to Sunday, from 10 am until 9pm. Asian taste also has its own tagline which is “Enjoy your favourite noodles with us” which gives the meaning that we served foods that catered to their tastebuds. The company is owned by Nurjeha Binti Ramli, the sole proprietor of Asian Taste. The reason of the establishment of this restaurant is that we want to provide foods that are famous from around Asian country so that people don’t have to go far to taste and enjoy it. Asian Taste has managed to attract a huge crowd to come and enjoy noodles since the opening. Our menu is famous noodle dishes around Asia such as Mee Yin Yong, which are famous in China, Chicken Pho from Vietnam, and Miso Nikomi Udon from Japan. By providing them multiple choices, we can attract a wide range of customers and many would come to dine in our restaurant. Our restaurant also available for online purchasing as we want to follow the buying trend and encourage people to stay at home during the pandemic. This business dedicated to share the taste of Asian to Malaysian and providing them with famous dishes from multiple country. Next, we are focusing on excellent customer service in return of high customer satisfaction. We hired professional and trained staff to make sure that the quality of our service is at the best. We also offered delicious foods on a lower price point to attract more customers into our restaurants and sustaining the relationship with them.